2016
DOI: 10.5588/pha.15.0054
|View full text |Cite
|
Sign up to set email alerts
|

Perception and intentions to quit among waterpipe smokers in Qatar: a cross-sectional survey

Abstract: A large proportion of shisha smokers viewed shisha as a safer alternative to cigarettes, yet they admitted to intending to quit. These findings underscore the need to design educational interventions and awareness campaigns as well as impose stringent laws on waterpipe smoking in public places in Qatar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…Relatively, higher proportion of students (69.9%) acknowledged that shisha smoking was associated with heart diseases, consistent with the findings of a previous study conducted in Malaysia (AL-Naggar and Saghir, 2011). Earlier studies conducted in Saudi Arabia (Amin et al, 2010), Malaysia (AL-Naggar and Saghir, 2011) and Qatar (Jaam et al, 2016) are in agreement to the findings of the current study that the participants did not have adequate knowledge about different health complications such as cancer, gum diseases, sexual problems, stroke etc. related to shisha smoking.…”
Section: Discussionsupporting
confidence: 91%
“…Relatively, higher proportion of students (69.9%) acknowledged that shisha smoking was associated with heart diseases, consistent with the findings of a previous study conducted in Malaysia (AL-Naggar and Saghir, 2011). Earlier studies conducted in Saudi Arabia (Amin et al, 2010), Malaysia (AL-Naggar and Saghir, 2011) and Qatar (Jaam et al, 2016) are in agreement to the findings of the current study that the participants did not have adequate knowledge about different health complications such as cancer, gum diseases, sexual problems, stroke etc. related to shisha smoking.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of STS from the study was substantially higher than the prevalence of 12.6% which had reported in 2008 among a sample from the same university (Taha et al, 2010); the finding indicates a noticeable increase in shisha use over the time. Similarly, a high prevalence of STS among students was also reported from universities in Al Madinah and Riyadh regions of Saudi Arabia (Awan et al, 2016;Daradka et al, 2019), in other countries in the Eastern Mediterranean Region (Roohafza et al, 2015;Jaam et al, 2016;Tucktuck et al, 2018). The current estimate was also higher than that among the general adult population in Saudi Arabia (Al Nomay and E Ahmed, 2015).…”
Section: Discussionsupporting
confidence: 68%
“…A cross-sectional study (2015) of male students from a university in the central region of Saudi Arabia reported that knowledge about the health hazards of STS was low among the students (Awan et al, 2016). Studies from neighboring countries of Saudi Arabia, which were conducted among young shisha users, observed that a substantial proportion of the shisha users viewed shisha as a safer alternative to cigarettes (Jaam et al, 2016;Abu-Rmeileh et al, 2018). Lack of effective interventions that target young population, who smoke shisha, is a serious public health concern in Saudi Arabia (Maziak et al, 2015a).…”
Section: Research Articlementioning
confidence: 99%
“…including United States [4,[22][23][29][30][31][32][33][34][35][36][37][38], United Kingdom [21,[39][40][41][42][43], Germany [6,44], Iran [45][46], Egypt [47][48], Malaysia [49], India [50], Dutch [51], Pakistan [52], Qatar [53], Jordan [10], Lebanon [54], Syria [55], Turkey [56], Bahrain [57], Israel [58], United Arab Emirates [22], Saudi Arabia [59],…”
Section: Resultsmentioning
confidence: 99%
“…In fact, some studies reported that taxation is effective in controlling tobacco smoking [53-54, 65, and 85]. However, Jaam [53], and Maziak [86] showed that cheap or expensive prices may not be effective in controlling WPS. Several studies suggested that executive authorities have main roles in controlling WPS, and they should be supported by legislative enforcers and policy makers [21, 23, and 87].…”
Section: Discussionmentioning
confidence: 99%